Topical Piroxicam and Conjunctivitis - Panida Kosrirukvongs (2018)
The study of comparison of the clinical responses of acute hemorrhagic conjunctivitis to antibiotic eye drops alone and combined with topical piroxicam was analyzed. Seventy-five patients (146 eyes) with viral conjunctivitis were randomly assigned to receive topical antibiotic (35 cases) or antibiotic combined with piroxicam eye drops (40 cases). The patients were examined under slit lamp biomicroscope every other day for the first week, then twice a week until recovery. There was no statistically significant difference between groups in mean age, sex, bilaterality, history of contact, systemic involvement, mean incubation period, mean onset and mean follow-up time. Mean recovery time in the piroxicam group (4.9 days) was less than for the control group (P=0.003). Foreign body sensation, pain and tearing in the piroxicam group recovered significantly faster than in the control group. Complete recovery of all symptoms and signs in piroxicam treated eyes (61%) was significantly more common than with antibiotic only (29%) in spite of more drug induced burning. Piroxicam eye drops may have beneficial effects for acute hemorrhagic conjunctivitis to relieve discomfort, pain, and accelerate recovery.